The Role of Plasma Trough Concentration of Voriconazole and Voriconazole N-Oxide in Its Hepatotoxicity in Adult Patients - Cheng L; You X; Wang X; Yu M; Jia C (Dove Medical Press, 2024)
Lin Cheng, Xi You, Xiaowen Wang, Mingjie Yu, Changsheng Jia Department of Pharmacy, the First Affiliated Hospital of Army Medical University, Chongqing, People's Republic of ChinaCorrespondence: Lin Cheng; Mingjie Yu, Email cheng7zhu@163.com; ymjxnyy@163.comObjective: Hepatotoxicity is an important cause of early withdrawal of voriconazole (VCZ). The role of the plasma trough concentration of VCZ (C0) in hepatotoxicity is confusion. VCZ N-oxide is the primary metabolite of VCZ in plasma. We investigated the role of VCZ C0 and plasma trough concentration of VCZ N-oxide (CN) in hepatotoxicity in adult patients.Materials and Methods: This was a prospective study. VCZ C0 and CN were measured using liquid chromatography-tandem mass spectrometry.Results: In total, 601 VCZ C0 and CN from 376 adult patients were included. The percentage of grade 1 or higher adverse events for ALP, ALT, AST, γ-GT, and TBIL were 35.4%, 21.0%, 30.1%, 56.2%, and 22.2%, respectively. Compared with younger adult patients, elderly patients (≥ 65 years) had a higher rate of grade 1 or higher adverse events of ALP. In the multivariate analysis, VCZ C0 was a risk factor for grade 1 or higher adverse events of AST in elderly patients and TBIL in younger adult patients, and VCZ CN was a risk factor for grade 1 or higher adverse events of ALT, AST, and TBIL. Results of the receiver operating characteristic curve analysis indicated that when the VCZ C0 was higher than 4.0 μg/mL, or the VCZ CN was lower than 1.7 μg/mL, the incidence of grade 1 or higher adverse events of AST and TBIL increased.Conclusion: VCZ C0 and CN were associated with liver function-related adverse events. Measurement of VCZ CN should be considered for VCZ therapeutic drug monitoring.Keywords: voriconazole, voriconazole N-oxide, hepatotoxicity, therapeutic drug monitoring